Efektifitas Konseling Individu dengan Teknik Self-talk pada Perilaku Prokrastinasi Mahasiswa Tingkat Akhir - Lestari, Yulian Sri (Program Studi Bimbingan dan Konseling Islam, 2024)
The background of many final year students who experience delays in doing their final project. Various reasons make the delay a comfortable but unfavorable condition for final students. This study aims to describe whether individual counseling services with self-talk techniques can have an influence on the procrastination behavior of final year students in doing their thesis. This research method uses experiments with one-group pretest-posttest design. There were 19 final year students. The data collection technique uses a Likert scale procrastination questionnaire. Data analysis uses the Wilcoxong test to determine differences before and after treatment. The results showed a change in student procrastination behavior indicated by a p value = 0.002 (<0.05) so that it can be concluded that there is an average difference between procrastination behavior on the pre-test and post-test so that it can be said that there is a significant influence between counseling with self-talk techniques on procrastination behavior.